Prader-Willi syndrome: a single center's experience in Korea - Yea Ji Kim; Chong Kun Cheon (Korean Pediatric Society, 2014)
PurposePrader-Willi syndrome (PWS) is a complex genetic disorder that results from the lack of paternally expressed genes in the chromosome 15q11-q13 region. This study was performed to delineate the clinical features of PWS infants and toddlers and the effects of two-year growth hormone (GH) treatment according to gender and age at the start of treatment.MethodsThe clinical characteristics and the results of the GH treatment were reviewed retrospectively for 30 PWS patients diagnosed by molecular genetic testing and clinical manifestations.ResultsThe mean age at diagnosis with PWS was 13.7 months (2-47 months of age). All patients showed the characteristics of facial dysmorphism, including brown hair and almond-shaped eyes. Most patients showed developmental delays/mental retardation (93.3%), cryptorchidism (75%), feeding problems in infancy (73.3%), and neonatal or infantile hypotonia (66.7%). Among 30 patients, 14 PWS infants and toddlers had been treated with GH for more than two years. Two years of GH treatment resulted in an improvement in head circumference-standard deviation score (HC-SDS), body weight-SDS, insulin-like growth factor-1 (IGF-1) SDS, IGF binding protein-3 (IGFBP-3) SDS, lean body mass, and bone mineral content, especially in IGFBP-3 SDS and motor development in PWS patients younger than two years of age. There was significant increase in IGF-1 SDS and IGFBP-3 SDS among male PWS patients after GH treatment.ConclusionOur study showed increases in IGFBP-3 SDS and an improvement in motor development among individuals under two years of age after GH treatment, and significant difference in IGF-1 SDS and IGFBP-3 SDS by gender.